Ancient Maya commerce: multidisciplinary research at Chunchucmil - Hutson, Scott R., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2017)
Using a variety of evidence--archaeological, botanical, geomorphological, and soil-based--contributors show how Chunchucmil, Yucatan, Mexico was a major center for both short and long distance trade, integrating the Guatemalan highlands, the Gulf of Mexico, and the interior of the northern Maya lowlands.--Provided by publisher.
Introduction / Scott R. Hutson and Bruce H. Dahlin -- Map of Chunchucmil / Scott Hutson and Aline Magnoni -- Architectural group typology and excavation sampling within Chunchucmil / Scott R. Hutson, Aline Magnoni, Bruce H. Dahlin -- Chunchucmil chronology and site dynamics / Socorro Jimenez, Aline Magnoni, Eugenia Mansell, and Tara Bond-Freeman -- Chunchucmil's urban population / Scott R. Hutson, Aline Magnoni, Traci Ardren, Chelsea Blackmore, and Travis Stanton -- Environmental heterogeneity in the Chunchucmil economic region / David Hixson, Timothy Beach, Sheryl Luzzadder-Beach and Bruce H. Dahlin -- Hydrology on the edge of the Chicxulub Crater: Chunchucmil and Uc-Cansahcab groundwater resources / Sheryl Luzzadder-Beach and Timothy Beach -- Hinterland settlement patterns within the Chunchucmil economic region / David R. Hixson and Daniel E. Mazeau -- Soils and agricultural carrying capacity / Timothy Beach, Sheryl Luzzadder-Beach, Ryan V. Sweetwood, Patrice Farrell, Daniel E. Mazeau, and Richard E. Terry -- Perishable resources produced for exchange in the Chunchucmil economic region / Bruce H. Dahlin, Traci Ardren, David R. Hixson, and Anthony P. Andrews -- Marketing within Chunchucmil / Scott R. Hutson, Richard E. Terry, and Bruce H. Dahlin -- Connections beyond Chunchucmil / Traci Ardren, Scott R. Hutson, David R. Hixson and Justin Lowry -- Conclusion / Scott R. Hutson.
Keywords: Excavations (Archaeology) -- Mexico -- Chunchucmil Site; Mayas -- Antiquities; Mayas -- Economic conditions; Mayas -- Commerce; Chunchucmil Site (Mexico); Mexico -- Antiquities